Facile and cost-effective methodology to fabricate MoS2 counter electrode for efficient dye-sensitized solar cells. (April 2018) - Vikraman, Dhanasekaran; Patil, Supriya A.; Hussain, Sajjad; Mengal, Naveed; Kim, Hyun-Seok; Jeong, Sung Hoon; Jung, Jongwan; Kim, Hak-Sung; Park, Hui Joon
Abstract: Interests in the development of economical and high-efficiency counter electrodes (CEs) of dye-sensitized solar cell (DSSC) to replace the excessively cost and scarce platinum (Pt) CEs have been increased. In this report, we demonstrate a facile chemical bath deposition (CBD) route to prepare layered MoS2 /fluorine-doped tin oxide (FTO) films that directly act as the CEs of DSSCs. A DSSC containing the CBD-synthesized MoS2 /FTO CE (prepared at 0.03 M Mo source concentration, 90 °C bath temperature and 30 min deposition time) exhibits high power conversion efficiency (PCE) of 7.14%, which is approaching that of DSSC with Pt/FTO CE (8.73%). The electrocatalytic activity of the MoS2 /FTO and Pt/FTO CEs are discussed in detail with their cyclic voltammetry (CV), Tafel polarization curves, and electrochemical impedance spectra (EIS). The observed results indicate that our low-cost CE has a high electrocatalytic activity for the reduction of triiodide to iodide and a low charge transfer resistance at the electrolyte–electrode interface with a comparable state to that of a Pt/FTO CE. Graphical abstract: Highlights: Crystalline MoS2 thin layers are grown on FTO using chemical bath deposition (CBD) method. The structural and optical properties of the synthesized MoS2 layers are systematically investigated. The electrocatalytic activity of the CBD-synthesized MoS2 /FTO is discussed with their CV, Tafel and EIS curves. A DSSC containing the MoS2 /FTO CE exhibits high power conversion efficiency of 7.14%.